Solid‐State Alkaline Fuel Cell Performance of Pentablock Terpolymer with Methylpyrrolidinium Cations as Anion Exchange Membrane and Ionomer. Issue 5 (6th October 2020) - Hwang, M.; Sun, R.; Willis, C.; Elabd, Y. A.
Abstract: In this study, pentablock terpolymers with methylpyrrolidinium cations were characterized and investigated as anion exchange membranes and ionomers for solid‐state alkaline fuel cells. The pentablock terpolymer (with methylpyrrolidinium cations) membranes exhibited higher fuel cell power density and durability than commercial FuMA‐Tech (with quaternary ammonium cations) membranes at 30 °C, 100% relative humidity (RH). Optimization of the catalyst ink composition (i.e., solids and solvent ratio) and fuel cell performance of membrane electrode assemblies (MEAs) with pentablock terpolymers as both the membrane and ionomer were also investigated. Optimization of the fuel cell operating conditions corroborates with the in situ electrochemical impedance spectroscopy results. The pentablock terpolymer MEA exhibited a maximum power density of 83.3 mW cm −2 and voltage decay rate of 0.7 mV h −1 after 100 h of operation under 40 °C, 100% RH. These results show promise for pentablock terptolymers with methylpyrrolidinium cations as a commercially attractive low‐cost alternative anion exchange membrane and ionomer for solid‐state alkaline fuel cells.